Silicon-boron flame retardant for PE (polyethylene) matrix, preparation method of silicon-boron flame retardant and PE-based composite material
Siborooxane prepared by ultrasonic treatment in a mixture of ethanol and water and reacting with ethyl orthosilicate and phenylboric acid, combined with PE-g-GMA, the flame retardant of silicon boron flame retardant in high temperature environment is solved. The problems of insufficient effect and poor dispersion improve the mechanical and flame retardant properties of PE matrix materials.
Patent Information
- Application Number
- CN202411321988.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-10
AI Technical Summary
The existing boro silicon flame retardant is insufficient in high temperature or high oxygen index environments, and its dispersion in polymer matrix is poor, resulting in a degradation of the mechanical properties of the material.
The silane hydrolysate is prepared by sonication in a mixture of ethanol and water at pH 2 to 7, and then reacts with ethyl orthosilicate and phenylboric acid in an organic solvent to form a silicon borooxane solution, and then with PE-g- GMA is stirred at a specific temperature and time range to obtain a high compatibility boron silicon flame retardant.
The mechanical properties and flame retardant properties of PE matrix materials are improved, and the uniform dispersion of flame retardant is ensured and the efficient and synergistic flame retardant effect of flame retardant is shown, especially in high temperature environments.
Smart Images

Figure BDA0005054252120000021 
Figure BDA0005054252120000022 
Figure BDA0005054252120000031
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardants, and in particular to a silicon-boron flame retardant for a PE matrix, a preparation method thereof, and a PE-based composite material. Background Art
[0002] Polyethylene (PE) has good mechanical properties, chemical stability and cost-effectiveness, and is widely used in packaging, pipes, wire and cable sheaths, household appliances and other fields. However, a significant drawback of polyethylene is its high flammability. It is very easy to burn and release a large amount of heat and toxic gases, posing a huge hidden danger to personal and property safety. Therefore, how to improve the flame retardant properties of polyethylene materials has become an important topic in the field of polyethylene applications.
[0003] The common method to improve the flame retardant properties of polyethylene is to add flame retardants to polyethylene. According to different flame retardant mechanisms, flame retardants can be divided into the following categories: (1) Halogen flame retardants: They mainly interrupt the combustion chain reaction by releasing halogen free radicals. Although their flame retardant effect is remarkable, the corrosive and toxic smoke produced during combustion have gradually restricted them in today's increasingly stringent environmental regulations. (2) Inorganic flame retardants: Such as aluminum hydroxide (ATH) and magnesium hydroxide (MH), they play a flame retardant role by absorbing heat and releasing water vapor at high temperatures to dilute the combustible gas. This type of flame retardant is safe and non-toxic, but its large addition amount can easily lead to a decrease in the mechanical properties of the material. (3) Phosphorus-based flame retardants: Such as red phosphorus, phosphonates, etc., they isolate heat and oxygen by promoting the formation of a protective carbon layer, capture H, OH free radicals, inhibit the combustion chain reaction, thereby reducing the flame temperature and slowing down the combustion rate. (4) Nitrogen-based flame retardants: Such as melamine and its derivatives, they mainly achieve flame retardant effects by absorbing heat and decomposing and releasing non-combustible gases to dilute the combustible gas. Its advantage is that it has significant synergistic effects with other flame retardants, but its effect is limited when used alone. (5) Silicone flame retardants: Silicon flame retardants will decompose and produce silicon oxides during the combustion process. These substances form a protective shell on the surface of the polymer, which has excellent heat insulation and oxygen isolation effects, and can effectively prevent the transfer of heat and oxygen, thereby slowing down the decomposition and combustion of the polymer. The protective layer can also prevent the phenomenon of molten dripping, reduce the spread of flames and secondary combustion caused by dripping. The current research trend not only focuses on the development of single flame retardants, but also pays more attention to the construction of composite flame retardant systems to achieve more efficient flame retardant effects and better comprehensive performance, especially the synergistic research of environmentally friendly flame retardants. It is well known that halogen flame retardants have gradually been banned from use in some fields because they produce a large amount of toxic gases during combustion. Although the toxicity of nitrogen and phosphorus flame retardants is lower than that of halogen flame retardants, they release acidic substances after combustion, so they cannot be used in some fields with high toxicity requirements, such as communication cable sheath materials. Therefore, inorganic flame retardants and silicon boron flame retardants are currently the most environmentally friendly flame retardants. Among them, the introduction of boron element into silicon flame retardant will cause the silicon-boron flame retardant to decompose at high temperature to generate boron oxide and silicon dioxide, forming a denser glass-like protective layer on the surface of polyethylene. This protective layer has a high-temperature isolation effect, which can effectively prevent the transfer of heat and oxygen, and block the release of toxic gases during combustion, slowing down and inhibiting the combustion of polyethylene.
[0004] Although existing silicon boron flame retardants can improve the flame retardancy of materials to a certain extent, their flame retardant effect may not be ideal in some high-demand applications. For example, in high temperature or high oxygen index environments, the flame retardant effect may be insufficient; and the dispersion of silicon boron flame retardants in polymer matrices is often poor, and they are easy to aggregate, resulting in a decrease in the mechanical properties of the material. Summary of the invention
[0005] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a silicon-boron flame retardant for a PE matrix, wherein the prepared silicon-boron flame retardant has good compatibility with the PE matrix and can improve the mechanical properties and flame retardant properties of the composite material.
[0006] Another object of the present invention is to provide a silicon-boron flame retardant for a PE matrix prepared by the above preparation method.
[0007] Another object of the present invention is to provide a PE-based composite material.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] The present invention provides a method for preparing a silicon-boron flame retardant for a PE substrate, comprising the following steps:
[0010] (1) adding diethoxydiphenylsiloxane to a mixture of ethanol and water at a pH of 2 to 7, and preparing a silane hydrolyzate after ultrasonic treatment;
[0011] The reaction equation is as follows:
[0012]
[0013] (2) dissolving ethyl orthosilicate and phenylboric acid in an organic solvent, and then dropping the mixture into the silane hydrolyzate prepared in step (1), stirring and reacting at 80 to 140° C. for 2 to 9 hours, and cooling to room temperature to obtain a silanoloxane solution; the reaction equation is as follows:
[0014]
[0015] (3) dissolving PE-g-GMA in an organic solvent to obtain a PE-g-GMA solution; slowly dropping the silicon boroxane solution obtained in step (2) into the PE-g-GMA solution, stirring at 20 to 90° C. for 5 to 14 hours, then rotary evaporating, washing, and drying to obtain a silicon boron flame retardant for a PE matrix; the stirring time is preferably
[0016] The reaction equation is as follows:
[0017]
[0018] Preferably, the organic solvent is toluene.
[0019] Preferably, in step (1), the volume ratio of ethanol to water is 5-9:1-5; more preferably 4:25; the pH value is 5; and the ultrasonic treatment time is 40-120 min, more preferably 90 min.
[0020] Preferably, in step (2), the mass ratio of the tetraethyl orthosilicate to diethoxydiphenylsiloxane is 2-6:22-28; the mass ratio of the tetraethyl orthosilicate, phenylboric acid and organic solvent is 2-6:5-16:18-29; more preferably 4:13:23; the stirring is mechanical stirring, the reaction temperature is 120°C; and the reaction time is 7h.
[0021] Preferably, in step (3), the mass ratio of PE-g-GMA to organic solvent is 7-15:18-22, more preferably 9:20; the mass ratio of PE-g-GMA to diethoxydiphenylsiloxane is 6-25:3-19, more preferably 19:9; the stirring is mechanical stirring, the temperature is 65°C, and the time is 10 hours.
[0022] Preferably, in step (3), the rotary evaporation temperature is 110-120° C., preferably 115° C.; deionized water is used for washing, and the product is dried at 80° C. to constant weight.
[0023] The present invention also provides a silicon-boron flame retardant for a PE substrate, which is prepared by the preparation method of the silicon-boron flame retardant for a PE substrate.
[0024] The present invention also provides a PE-based composite material, comprising 30-60 parts of the silicon-boron flame retardant for PE matrix, 60-110 parts of PE, 0.2-0.8 parts of a primary antioxidant, 0.1-0.3 parts of an auxiliary antioxidant, and 0.2-0.5 parts of a lubricant.
[0025] Preferably, the primary antioxidant is at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
[0026] Preferably, the auxiliary antioxidant is at least one of tris[2,4-di-tert-butylphenyl]phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, and dilauryl thiodipropionate.
[0027] Preferably, the lubricant is at least one of zinc stearate and polyethylene wax.
[0028] Preferably, the PE-based composite material is prepared by the following method:
[0029] PE, silicon-boron flame retardant, primary antioxidant, auxiliary antioxidant and lubricant are mixed in a mixer to obtain a mixture, which is then mixed in an internal mixer, and the obtained rubber material is extruded in a twin-screw extruder to obtain a PE / GSiB composite material;
[0030] The temperature setting range of the internal mixer is 160-230°C, preferably 170°C;
[0031] The temperature setting range of the twin-screw extruder is 160-230°C, preferably 170°C.
[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0033] The method for preparing a silicon boron flame retardant for a PE matrix of the present invention utilizes the epoxy group of a PE graft PE-g-GMA to react with the hydroxyl group on silicon boroxane to synthesize a high-efficiency silicon boron flame retardant. The prepared silicon boron flame retardant has good compatibility with the PE matrix, thereby improving the mechanical properties of the composite material; and also ensures uniform dispersion of the flame retardant in the matrix, thereby improving the flame retardant properties of the composite material through the synergistic flame retardant effect of silicon boron. DETAILED DESCRIPTION
[0034] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0035] The mechanical property test specimens in the present invention are prepared by injection molding, and the specific method is: placing the EVA / Mg(OH)2 composite material in an injection molding machine at 170-230°C, preparing tensile and flame retardant test specimens according to national standards GB / T 1040.1-2018, GB / T2406.2-2009, and GB / T2408-2008, and testing them according to the standards.
[0036] The PE used in the following examples was purchased from ExxonMobil Chemical Co., Ltd., with the brand number 3518CB.
[0037] Example 1
[0038] The preparation method of the silicon boron flame retardant of this embodiment is as follows:
[0039] (1) 90 mL of ethanol and 10 mL of deionized water were fully mixed. The pH of the mixture was then adjusted to 2 with acetic acid. Thereafter, 5 g of diethoxydiphenylsiloxane was added to the solution and ultrasonicated for 40 min to obtain a silane hydrolyzate.
[0040] (2) 1.0 g of ethyl orthosilicate and 9.0 g of phenylboric acid were dissolved in 14.0 mL of toluene, and the mixture was slowly added dropwise to the silane hydrolyzate solution. The mixture was reacted at 110° C. with mechanical stirring for 6 h, and then cooled to room temperature.
[0041] (3) 41.6 g of PE-g-GMA was dissolved in 14 mL of toluene, and the silanol toluene solution obtained in step (2) was slowly added dropwise to the PE-g-GMA toluene solution, and mechanically stirred at 90° C. for 10 h, followed by rotary evaporation, washing, and drying to obtain the product GSiB.
[0042] The preparation method of PE / GSiB composite material is as follows:
[0043] 80g PE, 20g flame retardant GSiB, 0.5g pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 0.3g tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168) and 0.4g zinc stearate were mixed in a mixer to obtain a mixture, which was added into a 170°C internal mixer for internal mixing. The obtained rubber material was extruded and granulated in a twin-screw extruder to obtain PE / GSiB composite material particles, and then the PE / GSiB composite material particles were injection-molded into standard specimens for testing.
[0044] Example 2
[0045] The preparation method of the silicon boron flame retardant of this embodiment is as follows:
[0046] (1) 90 mL of ethanol and 10 mL of deionized water were fully mixed. The pH of the mixture was then adjusted to 3 with acetic acid. Thereafter, 7 g of diethoxydiphenylsiloxane was added to the solution and ultrasonicated for 110 min to obtain a silane hydrolyzate.
[0047] (2) 2.3 g of ethyl orthosilicate and 5.8 g of phenylboric acid were dissolved in 14.0 mL of toluene, and the mixture was slowly added dropwise to the silane hydrolyzate solution. The mixture was reacted at 80° C. with mechanical stirring for 9 h, and then cooled to room temperature.
[0048] (3) 21.3 g of PE-g-GMA was dissolved in 14 mL of toluene, and the silanol toluene solution obtained in step (2) was slowly added dropwise to the PE-g-GMA toluene solution, and mechanically stirred at 90° C. for 11 h, followed by rotary evaporation, washing, and drying to obtain the product GSiB.
[0049] The preparation method of PE / GSiB composite material is as follows:
[0050] 75g PE, 502g flame retardant GSiB, 0.5g pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 0.3g tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168) and 0.4g zinc stearate were mixed in a mixer to obtain a mixture, which was added into a 170°C internal mixer for internal mixing. The obtained rubber material was extruded and granulated in a twin-screw extruder to obtain PE / GSiB composite material particles, and then the PE / GSiB composite material particles were injection-molded into standard specimens for testing.
[0051] Example 3
[0052] The preparation method of the silicon boron flame retardant of this embodiment is as follows:
[0053] (1) 90 mL of ethanol and 10 mL of deionized water were fully mixed. The pH of the mixture was then adjusted to 4 with acetic acid. Thereafter, 9.0 g of diethoxydiphenylsiloxane was added to the solution and ultrasonicated for 120 min to obtain a silane hydrolyzate.
[0054] (2) 1.8 g of ethyl orthosilicate and 10.2 g of phenylboric acid were dissolved in 14.0 mL of toluene, and the mixture was slowly added dropwise to the silane hydrolyzate solution. The mixture was mechanically stirred at 140° C. for 2 h, and then cooled to room temperature.
[0055] (3) 24.8 g of PE-g-GMA was dissolved in 14 mL of toluene, and the silanol toluene solution obtained in step (2) was slowly added dropwise to the PE-g-GMA toluene solution, and mechanically stirred at 20° C. for 14 h, followed by rotary evaporation, washing, and drying to obtain the product GSiB.
[0056] The preparation method of PE / GSiB composite material is as follows:
[0057] 70g PE, 30g flame retardant GSiB, 0.5g pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 0.3g tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168) and 0.4g zinc stearate were mixed in a mixer to obtain a mixture, which was added into a 170°C internal mixer for internal mixing. The obtained rubber material was extruded and granulated in a twin-screw extruder to obtain PE / GSiB composite material particles, and then the PE / GSiB composite material particles were injection-molded into standard specimens for testing.
[0058] Example 4
[0059] The preparation method of the silicon boron flame retardant of this embodiment is as follows:
[0060] (1) 90 mL of ethanol and 10 mL of deionized water were fully mixed. The pH of the mixture was then adjusted to 7 with acetic acid. Thereafter, 15 g of diethoxydiphenylsiloxane was added to the solution and ultrasonicated for 90 min to obtain a silane hydrolyzate.
[0061] (2) 2.4 g of ethyl orthosilicate and 7.8 g of phenylboric acid were dissolved in 14.0 mL of toluene, and the mixture was slowly added dropwise to the silane hydrolyzate solution. The mixture was reacted at 120° C. with mechanical stirring for 7 h, and then cooled to room temperature.
[0062] (3) 31.6 g of PE-g-GMA was dissolved in 14 mL of toluene, and the silanol toluene solution obtained in step (2) was slowly added dropwise to the PE-g-GMA toluene solution, and mechanically stirred at 65° C. for 10 h, followed by rotary evaporation, washing, and drying to obtain the product GSiB.
[0063] The preparation method of PE / GSiB composite material is as follows:
[0064] 65g PE, 35g flame retardant GSiB, 0.5g pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 0.3g tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168) and 0.4g zinc stearate were mixed in a mixer to obtain a mixture, which was added into a 170°C internal mixer for internal mixing. The obtained rubber material was extruded and granulated in a twin-screw extruder to obtain PE / GSiB composite material particles, and then the PE / GSiB composite material particles were injection-molded into standard specimens for testing.
[0065] Example 5
[0066] The preparation method of the silicon boron flame retardant of this embodiment is as follows:
[0067] (1) 90 mL of ethanol and 10 mL of deionized water were fully mixed. The pH of the mixture was then adjusted to 5 with acetic acid. Thereafter, 11.0 g of diethoxydiphenylsiloxane was added to the solution and ultrasonicated for 50 min to obtain a silane hydrolyzate.
[0068] (2) 2.2 g of ethyl orthosilicate and 12.5 g of phenylboric acid were dissolved in 14.0 mL of toluene, and the mixture was slowly added dropwise to the silane hydrolyzate solution. The mixture was mechanically stirred at 90° C. for 9 h, and then cooled to room temperature.
[0069] (3) 25.7 g of PE-g-GMA was dissolved in 14 mL of toluene, and the silanol toluene solution obtained in step (2) was slowly added dropwise to the PE-g-GMA toluene solution, and mechanically stirred at 80° C. for 9 h, followed by rotary evaporation, washing, and drying to obtain the product GSiB.
[0070] The preparation method of PE / GSiB composite material is as follows:
[0071] 60g PE, 40g flame retardant GSiB, 0.5g pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 0.3g tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168) and 0.4g zinc stearate were mixed in a mixer to obtain a mixture, which was added into a 170°C internal mixer for internal mixing. The obtained rubber material was extruded and granulated in a twin-screw extruder to obtain PE / GSiB composite material particles, and then the PE / GSiB composite material particles were injection-molded into standard specimens for testing.
[0072] Example 6
[0073] The preparation method of the silicon boron flame retardant of this embodiment is as follows:
[0074] (1) 90 mL of ethanol and 10 mL of deionized water were fully mixed. The pH of the mixture was then adjusted to 6 with acetic acid. Thereafter, 17.0 g of diethoxydiphenylsiloxane was added to the solution and ultrasonicated for 90 min to obtain a silane hydrolyzate.
[0075] (2) 3.1 g of ethyl orthosilicate and 17.5 g of phenylboric acid were dissolved in 14.0 mL of toluene, and the mixture was slowly added dropwise to the silane hydrolyzate solution. The mixture was reacted at 140° C. with mechanical stirring for 2 h, and then cooled to room temperature.
[0076] (3) 15.3 g of PE-g-GMA was dissolved in 14 mL of toluene, and the silanol toluene solution obtained in step (2) was slowly added dropwise to the PE-g-GMA toluene solution, and mechanically stirred at 65° C. for 10 h, followed by rotary evaporation, washing, and drying to obtain the product GSiB.
[0077] The preparation method of PE / GSiB composite material is as follows:
[0078] 55g PE, 45g flame retardant GSiB, 0.5g pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 0.3g tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168) and 0.4g zinc stearate were mixed in a mixer to obtain a mixture, which was added into a 170°C internal mixer for internal mixing. The obtained rubber material was extruded and granulated in a twin-screw extruder to obtain PE / GSiB composite material particles, and then the PE / GSiB composite material particles were injection-molded into standard specimens for testing.
[0079] Example 7
[0080] The preparation method of the silicon boron flame retardant of this embodiment is as follows:
[0081] (1) 90 mL of ethanol and 10 mL of deionized water were fully mixed. The pH of the mixture was then adjusted to 7 with acetic acid. Thereafter, 17.0 g of diethoxydiphenylsiloxane was added to the solution and ultrasonicated for 60 min to obtain a silane hydrolyzate.
[0082] (2) 1.4 g of ethyl orthosilicate and 7.9 g of phenylboric acid were dissolved in 14.0 mL of toluene, and the mixture was slowly added dropwise to the silane hydrolyzate solution. The mixture was reacted at 130° C. with mechanical stirring for 10 h, and then cooled to room temperature.
[0083] (3) 10.0 g of PE-g-GMA was dissolved in 14 mL of toluene, and the silanol toluene solution obtained in step (2) was slowly added dropwise to the PE-g-GMA toluene solution, and mechanically stirred at 90° C. for 11 h, followed by rotary evaporation, washing, and drying to obtain the product GSiB.
[0084] The preparation method of PE / GSiB composite material is as follows:
[0085] 50g PE, 50g flame retardant GSiB, 0.5g pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 0.3g tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168) and 0.4g zinc stearate were mixed in a mixer to obtain a mixture, which was added into a 170°C internal mixer for internal mixing. The obtained rubber material was extruded and granulated in a twin-screw extruder to obtain PE / GSiB composite material particles, and then the PE / GSiB composite material particles were injection-molded into standard specimens for testing.
[0086] Example 8
[0087] The preparation method of the silicon boron flame retardant of this embodiment is as follows:
[0088] (1) 90 mL of ethanol and 10 mL of deionized water were fully mixed. The pH of the mixture was then adjusted to 5 with acetic acid. Thereafter, 13.0 g of diethoxydiphenylsiloxane was added to the solution and ultrasonicated for 120 min to obtain a silane hydrolyzate.
[0089] (2) 3.5 g of ethyl orthosilicate and 19.8 g of phenylboric acid were dissolved in 14.0 mL of toluene, and the mixture was slowly added dropwise to the silane hydrolyzate solution. The mixture was reacted at 140° C. with mechanical stirring for 2 h, and then cooled to room temperature.
[0090] (3) 39.2 g of PE-g-GMA was dissolved in 14 mL of toluene, and the silanol toluene solution obtained in step (2) was slowly added dropwise to the PE-g-GMA toluene solution, and mechanically stirred at 30° C. for 13 h, followed by rotary evaporation, washing, and drying to obtain the product GSiB.
[0091] The preparation method of PE / GSiB composite material is as follows:
[0092] 45g PE, 55g flame retardant GSiB, 0.5g pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 0.3g tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168) and 0.4g zinc stearate were mixed in a mixer to obtain a mixture, which was added into a 170°C internal mixer for internal mixing. The obtained rubber material was extruded and granulated in a twin-screw extruder to obtain PE / GSiB composite material particles, and then the PE / GSiB composite material particles were injection-molded into standard specimens for testing.
[0093] Comparative Example 1
[0094] The preparation method of PE composite material is as follows:
[0095] 100g PE, 0.5g pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 0.3g tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168) and 0.4g polyethylene wax were mixed in a mixer to obtain a mixture, which was added into a 170°C internal mixer for internal mixing. The obtained rubber compound was extruded and granulated in a twin-screw extruder to obtain PE / Mg(OH)2 composite material particles, and then the PE composite material particles were injection-molded into standard specimens for testing.
[0096] Comparative Example 2
[0097] The preparation method of PE / Al(OH)3 composite material is as follows:
[0098] 65g PE, 35g magnesium hydroxide, 0.5g pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010), 0.3g tris[2,4-di-tert-butylphenyl] phosphite (antioxidant 168) and 0.4g polyethylene wax were mixed in a mixer to obtain a mixture, which was added into a 170°C internal mixer for internal mixing. The obtained rubber material was extruded and granulated in a twin-screw extruder to obtain PE / Al(OH)3 composite material particles, and then the PE / Al(OH)3 composite material particles were injection-molded into standard specimens for testing.
[0099] The relevant test results of the PE composite material prepared in Comparative Example 1, the PE / Al(OH)3 composite material prepared in Comparative Example 2 and the PE / GSiB composite material prepared in Examples 1-8 are as follows:
[0100] Table 1 Related test results
[0101]
[0102] It can be seen from the test results in Table 1 that, since the epoxy group of the PE graft PE-g-GMA is used to react with the hydroxyl group on the silicon boroxane to undergo a ring-opening addition reaction to synthesize a high-efficiency silicon boron flame retardant GSiB, the silicon boron flame retardant contains a group that can react chemically with PE on its surface, and directly undergoes a chemical grafting reaction with PE during the processing, so the flame retardant has improved compatibility with the matrix PE, thereby improving the mechanical properties of the composite material; due to the improved compatibility between the flame retardant and the matrix, the dispersibility of the flame retardant in the matrix is also improved, thereby ensuring the uniform dispersion of the flame retardant in the matrix, and improving the flame retardant properties of the composite material through the synergistic flame retardant effect of silicon boron, and Example 4 has the best performance.
[0103] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a silicon-boron flame retardant for a PE substrate, characterized in that: The following steps are involved: (1) adding diethoxydiphenylsiloxane to a mixture of ethanol and water at a pH of 2 to 7 to prepare a silane hydrolyzate; (2) dissolving ethyl orthosilicate and phenylboric acid in an organic solvent, and then adding dropwise to the silane hydrolyzate prepared in step (1), reacting at 80 to 140° C. for 2 to 9 hours, and cooling to room temperature to obtain a silanoloxane solution; (3) dissolving PE-g-GMA in an organic solvent to obtain a PE-g-GMA solution; adding the silicon boroxane solution obtained in step (2) dropwise to the PE-g-GMA solution, stirring at 20 to 90° C. for 5 to 14 hours, and then rotary evaporating, washing, and drying to obtain a silicon boron flame retardant for a PE matrix.
2. The method for preparing a silicon-boron flame retardant for a PE substrate according to claim 1, characterized in that: The organic solvent is toluene.
3. The method for preparing a silicon-boron flame retardant for a PE substrate according to claim 1, characterized in that: In step (1), the volume ratio of ethanol to water is 5-9:1-5.
4. The method for preparing a silicon-boron flame retardant for a PE substrate according to claim 1, characterized in that: In step (2), the mass ratio of the tetraethyl orthosilicate to diethoxydiphenylsiloxane is 2-6:22-28; the mass ratio of the tetraethyl orthosilicate, phenylboric acid and organic solvent is 2-6:5-16:18-29.
5. The method for preparing a silicon-boron flame retardant for a PE substrate according to claim 1, characterized in that: In step (3), the mass ratio of the PE-g-GMA to the organic solvent is 7-15:18-22; the mass ratio of the PE-g-GMA to diethoxydiphenylsiloxane is 6-25:3-19.
6. Silicon boron flame retardant for PE matrix, characterized in that: The silicon-boron flame retardant is prepared by the preparation method of the silicon-boron flame retardant for PE substrate according to any one of claims 1 to 5.
7. PE-based composite material, characterized in that: The invention comprises 30-60 parts of the silicon-boron flame retardant for PE substrate as claimed in claim 6, 60-110 parts of PE, 0.2-0.8 parts of a primary antioxidant, 0.1-0.3 parts of an auxiliary antioxidant and 0.2-0.5 parts of a lubricant.
8. The PE-based composite material according to claim 7, characterized in that: The primary antioxidant is at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.
9. The PE-based composite material according to claim 7, characterized in that: The auxiliary antioxidant is at least one of tris[2,4-di-tert-butylphenyl]phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite and dilauryl thiodipropionate.
10. The PE-based composite material according to claim 7, characterized in that: The lubricant is at least one of zinc stearate and polyethylene wax.
Citation Information
Cited By
Corrosion-resistant polypropylene edge band material and preparation method thereof
CN119823494A